MobilePay versus Swipp - Main insights from a Nordic country for mobile payment apps - Karl-Heinz Moritz; Georg Stadtmann; Tobias Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2018)
We describe the development of the market for mobile payments in Denmark. In the first step, we explain the two main competing products as well as their underlying technologies. In the second step, we also analyze the competition within the Danish market from debit card companies and the competition which stems from outside of the banking industry (Apple Pay). Based on our analysis, we derive some managerial as well as policy implications.
Keywords: B52; G21; L86; 330; FinTech; First-Mover Advantage; Open versus closed platforms; two sided markets; diffusion; market entry